Past incarceration and chlamydia infection among young Black men in New Orleans - Stapleton, Jenisha L.; Ratnayake, Aneeka; Gomes, Gérard; He, Hua; Kissinger, Patricia J. (Frontiers in Public Health, 2023)
Background: Young Black men are disproportionately and adversely affected by incarceration and sexually transmitted infections, both of which share common social and structural determinants. It is well documented that those incarcerated are more likely to acquire STIs in the carceral setting compared to the general population. However, the effects of imprisonment on sexual health outcomes after imprisonment are not well-understood. The relationship between incarceration history (having ever spent time in a correctional institution such as prison, jail, or juvenile detention) and chlamydia positivity was examined in this study. Methods: A secondary analysis of the Check it Program, a Chlamydia trachomatis (Ct) community-based seek, test, and treat screening program for Black men aged 15-24 who have sex with women in New Orleans was conducted. Participants completed a computer-assisted self-administered questionnaire on relevant sexual and social histories and provided a urine specimen for a Ct urine nucleic acid amplification test (NAAT). Bivariate and multivariable regressions were used to estimate the association between incarceration history and chlamydia positivity. Results: Participants (N=1,907) were enrolled from May 2017 to March 2020. Of those, 351/1,816 (19.3%) reported past incarceration and 203/1,888 (10.8%) tested positive for Ct. When adjusted for age, insurance, condom use, age at sexual debut, and the total number of female sexual partners, having a history of incarceration was positively associated with a positive Ct test (aOR (95% CI): 1.49 (1.03, 2.15), p=0.0095)). Conclusions: These findings suggest that interacting with the carceral system contributes to the increased odds of Ct post-incarceration, even after controlling for other known risk factors. Incarceration may be an important factor in Ct outcomes in young Black men and those with a history of incarceration should be prioritized for Ct screening after release.